The relationship between smoking during pregnancy and perceived social support, self-esteem and psychological resilience - Yalnız Dilcen, Hacer; Öztürk, Ayfer; Nebioğlu Yıldız, Melike (Journal of Dependence, 2021)
Objective: The aim of this study was to examine the relationship between the perceived social support, self-esteem and psychological resilience of pregnant women who smoke, according to various factors.Method: A total of 187 literate pregnant women over 18 years old who completed their 13th week, and agreed to participate were included in the study. Sociodemographic data form , Fagerström Nicotine Dependence Test, Rosenberg Self-Esteem Scale, Multidimensional Scale of Perceived Social Support, and Brief Psychological Resilience Scale were used in the study.Results: It was determined that 13% of them smoked in their current pregnancy. A statistically significant, positive and weak relationship was found between the perceived social support and self-esteem in pregnant women. When the addiction levels of pregnant women and their perceived social support scores were examined, the model was found to be statistically significant in term of the level of predicting self-esteem of pregnant women.Conclusion: Considering the possibility of transferring smoking addiction to future generations, prevention of smoking and passive smoking in all individuals, especially expectant mothers, should be considered as one of the important responsibilities of healthcare professionals and the society. It is especially important for healthcare professionals to provide awareness training on this issue.
Keywords: Pregnancy; smooking; perceived social support; self-esteem; psychological resilience